PENGARUH INSENTIF, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM KABUPATEN SUKOHARJO - Djuwarto, Istiatin, Sri Hartono (ITB AAS INDONESIA, 2017)
The purpose of this research are: 1) To determine the effect of incentive, competent, and working environment simultaneously on employee performance Dinas Pekerjaan Umum Kabupaten Sukoharjo. 2) To determine the effect of incentive, competence, and working environment on employee performance Dinas Pekerjaan Umum Kabupaten Sukoharjo.Data collection method used is the method of questionnaire / questionnaire to 50 employees as respondents. Sampling technique used is random sampling method convenionce sampling. Data analysis methods used include: test instrument (validity and reliability), hypothesis testing (multiple linear regression analysis, t-test, f and the coefficient of determination (R2).Results Descriptive analysis showed that most respondents gender male (82%). All data from the questionnaires have passed the test instrument. For testing f test result that the value of F (45.186)> F table (3.15) with a probability of 0.000 (p <0.05). This means Fhitung in the region of Ho rejected, which means a significant difference between the independent variable (incentive, competence, and working environment) simultaneously on the dependent variable (employee performance). From the results of the t test result incentive have a significant positive effect on an individual basis to variable employee performance. This is evident from tcount (5.907)> t table (2.000) with a significance value <α (0.05). Variable competence are also significant positive effect on employee performance. This is because tcount (2.919)> t table (2.000) with a significance value <α (0.05). Variable working environment is also significant positive effect on employee performance. This is because tcount (4.570)> t table (2.000) with a significance value <α (0.05). The results of the analysis in this study was obtained R2 values of 0.685 (68.5%). This means that the independent variable (incentive, competence, and working environment) able to contribute 68.5% influence on the dependent variable (employee performance). While the rest of 31.5% is influenced by other variables outside of this study as a leadership, compensation, organisational culture, etc.Keywords: Incentive, competence, working environment, employee performance